“Tracks which cannot be covered”: P.J. Schoeman and Public Intellectuals in Southern Africa (Historia, 2021)
EnglishP.J. Schoeman is largely ignored in the history of South African anthropology and apartheid, yet as this article shows, he played a significant role as a public intellectual. He felt so strongly about the importance of segregation that he unsuccessfully ran for Parliament as Cape African Representative and then was able to try to put his theory to practice as Chairman of the Commission for the Preservation of the Bushmen in South-West Africa. The theoretical paradigm he operated in was heavily tinged with Malinowskian functionalism. Schoeman’s experiences provide important insights for contemporary South African academics as they ponder their role as “public” or “citizen” intellectuals in the new South Africa.   Afrikaans“Tracks which cannot be covered”: P.J. Schoeman en Openbare Intellektuele in Suider-Afrika In die geskiedenis van Suid-Afrikaanse antropologie en apartheid, word P.J. Schoeman grotendeels geïgnoreer, maar soos hierdie artikel bewys, het hy tog ŉ noemenswaardige rol as openbare intellektueel vertolk. Hy het só sterk oor segregasie gevoel dat hy (weliswaar onsuksesvol) vir die parlementêre setel van Kaapse naturelleverteenwoordiger in die parlement gestaan het en daarna sy teorieë in die praktyk as voorsitter van die Kommissie vir die Behoud van die Boesmanbevolking in SuidwesAfrika beoefen het. Die teoretiese paradigma waarbinne hy opgetree het, is sterk deur Malinowski se funksionalisme beïnvloed. Schoeman se ondervinding is van waarde vir kontemporêre Suid-Afrikaanse akademici wanneer hulle hulle rol as “openbare” of “burgerlike” intellektuele in die nuwe Suid-Afrika oordink.
Keywords: Commission for the Preservation of the Bushmen; English-Afrikaans academic relations; Etosha Game Reserve; functionalism; Hai//om; Malinowski; nature literature; origins of apartheid; segregation; social anthropology; University of Stellenbosch; volkekunde; Engels-Afrikaanse akademiese verhoudings; Etosha-Wildreservaat; funksionalisme; Hai//omKommissie vir die Behoud van die Boesmanbevolking; Malinowskinatuurliteratuur; oorsprong van apartheid; segregasie; sosiale antropologie; Universiteit van Stellenbosch